Near electrode effects in magneto-electrochemistry - Dunne, Peter (Trinity College (Dublin, Ireland). School of Physics, 2011)
Magnetic fields imposed on electrochemical cells have been shown to have dramatic effects on electrodeposits ranging from surface morphology, crystal structure, deposition rate, alloy composition and magnetic properties. To further illuminate the effects of magnetic fields a number of electrochemical systems were studied ranging from metal deposition in uniform magnetic fields, organic liquid-liquid systems, and patterned metal deposits by permanent magnet arrays. Lorentz force induced magneto-convection was observed to dominate during metal electrodeposition and corrosion, enhancing the mass transport of ions by thinning the diffusion layer. Using AC impedance methods the double layer and charge transfer kinetics were probed in a model one electron transfer system. The imposition of a magnetic field was observed to alter the structure of the double layer and the measured apparent kinetics of the system. No true magnetic shift in kinetics was observed, rather all the effects are due to the change in free energy at the interface due to the magnetostatic energy, which is manifested as an induced Maxwell stress and thus the increased attraction of ions to the electrode surface. Patterned permanent magnet arrays were used to demonstrate magnetic templating using paramagnetic ions, inverse templating using rare-earth salts as contrast agents. The deposits were seen to follow the contours of |B|, which can be explained in terms of the magnetostatic interaction developed in the model system. Magnetic templating is a potentially fruitful development that may scale below the micron dimensions demonstrated here. In summary, all magnetic field effects in electrochemical systems can be described and understood through the determination of the energies involved. This avoids any erroneous derivation of forces from incorrect boundary condition assumptions, and can also take into account the magnetic stresses, or energies, which are ignored in a force model, where only net forces are considered.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin